Inhibitory Activity of Quercetin, Rutin, and Hyperoside against Xanthine Oxidase: Kinetics, Fluorescence, and Molecular Docking - Yu, Yali; Xiong, Yingzhu; Tong, Siman; Li, Yanli; Cai, Rongcan; Zhang, Xv; Gao, Feng (Current Pharmaceutical Biotechnology, 2025)
IntroductionQuercetin (Qc), rutin (Ru), and hyperoside (Hyp) are three common polyphenols widely distributed in the plant kingdom.MethodsThis study explored the inhibition and mechanisms of Qc, Ru, and Hyp against xanthine oxidase (XOD) by enzyme kinetic analysis, fluorescence analysis, and molecular docking. The inhibitory activities of the three polyphenols on XOD showed the following trend: quercetin > hyperoside > rutin, with IC50 values of 8.327 ± 0.36 µmol/L, 35.215 ± 0.4 µmol/L and 60.811 ± 0.19 µmol/L, respectively. All three polyphenols inhibited xanthine oxidase activity in a mixed-competitive manner. Synchronous fluorescence results demonstrated that three polyphenols binding to XOD were spontaneous and showed static quenching.ResultsThe binding of the three polyphenols to XOD is mainly driven by hydrogen bonding and van der Waals forces, resulting in the formation of an XOD-XA complex with only one affinity binding site. The binding sites of the three RSFQ phenolic compounds are close to those of tryptophan. Molecular docking showed that all three polyphenols enter the active pocket of XOD and maintain the stability of the complex through hydrogen bonding, hydrophobic interaction, and van der Waals forces.ConclusionThe results provide a theoretical basis for quercetin, rutin, and hyperoside to be used as function factors to prevent hyperuricemia.
Keywords: fluorescence analysis